PHARMACOLOGICAL INTERVENTIONS IN THE TREATMENT OF TRIGEMINAL NEURALGIA (TN), GLOSSOPHARYNGEAL NEURALGIA (GN) AND TRIGEMINAL AUTONOMIC CEPHALALGIAS (TAC) – A SYSTEMATIC REVIEW - CAROLINE SUNITHA K; M ARVIND (International Journal of Pharma and Bio Sciences, 2014)
Assessing the pain relieving effect of various pharmacological agents in the treatment of trigeminal neuralgia, glossopharyngeal neuralgia and trigeminal autonomic cephalalgias by carrying out a systematic review of literature. Materials and methods- Electronic search of the Pub Med –MeSH database was undertaken. Hand searches were taken from the back references. The search yielded a total of 14 articles out of which 4 met articles met the inclusion criteria and the other 10 articles were eliminated. The available literature shows that there is use of intranasal zolmitriptan, sumatriptan and high flow oxygen in the management of pain in trigeminal autonomic cephalalgias. In the treatment of trigeminal neuralgia, oxcarbazepine is the latest drug of known efficacy and safety. In the management of glossopharyngeal neuralgia, no randomised controlled trials were done but experimental studies reported better results with oxcarbazepine when compared to other drugs.